Epidemiology of gastric cancer in Japan. Issue 957 (5th July 2005) - Inoue, M; Tsugane, S
Abstract : Despite its decreasing trend in Japan, gastric cancer remains an important public health problem. Although the age standardised rates of gastric cancer have been declining for decades, the absolute numbers are increasing because of the rapid aging of the population. A large proportion of Japanese gastric cancers are detected at an early stage, with a better overall survival rate. As with Western developed countries, a change in the social environment such as reduced salt use and increased fresh vegetable and fruit intake as well as improvement of food storage may play an important part in the decline. Differences in Helicobacter pylori infection rates between generations presumably have contributed to the generation related variation in the declining trends. It is expected that most gastric cancers in Japan may be preventable by lifestyle modification such as salt reduction and increased fruit and vegetable intake, together with avoidance of smoking and countermeasures against H pylori infection so that the level now evident in Western developed countries can be reached.